Rituximab versus anti-TNF in patients who previously failed one TNF inhibitor in an observational cohort. (May 2013) - Chatzidionysiou, K; Vollenhoven, RF van
Abstract : Objective: The purpose of this study was to characterize and compare responses in patients who had failed one tumour necrosis factor (TNF) inhibitor when switching to another TNF inhibitor or rituximab (RTX). Methods: The Stockholm TNF follow-up registry (STURE) was used. Treatment results at 6 months were analysed by (i) the biologic used, (ii) the type of anti-TNF switch, and (iii) the reason for discontinuation (inefficacy or intolerance). Results: A total of 328 patients who failed an anti-TNF switched to an alternative biologic, 69 to RTX, 161 to an anti-TNF monoclonal antibody (mAb), and 98 to etanercept (ETA). Significant reductions in the 28-joint Disease Activity Score (DAS28) at 6 months were observed for all groups. The mean ± SD reduction in DAS28 was 1.70 ± 1.18 for RTX, 1.40 ± 1.51 for ETA, and 0.67 ± 1.36 for mAb, the difference being statistically significant between RTX and mAb (p < 0.0001). For patients who had failed ETA, RTX led to significantly greater DAS28 reductions than mAb (p = 0.01). When the reason for discontinuation of the previous anti-TNF was intolerance or secondary inefficacy, RTX led to significantly greater DAS28 reduction compared to mAb and ETA (p = 0.01 and p = 0.03, respectively). Conclusions: In this observational cohort, patients who failed one anti-TNF had better overall results when treated with RTX than with a subsequent anti-TNF mAb. Having failed ETA, RTX yielded greater DAS28 reductions and European League Against Rheumatism (EULAR) responses than mAb. The advantage of RTX was most clearly seen in patients who had failed anti-TNF because of intolerance or secondary inefficacy.